Shortage or surplus: economic and noneconomic approaches to the analysis of nursing labor markets. - Lane, Julia I.; Gohmann, Stephan F. (Southern Economic Journal, 1995)
A study finds that noneconomic estimates of the nursing shortage are substantially higher than economic estimates. Data from the Bureau of Health Professions on counties with short-term general hospitals were used to estimate the 1985 supply and demand for full-time-equivalent nurses, using both equilibrium and disequilibrium models. Regression results designate 423 of 1,880 counties as shortage areas, under the assumption that wages do not instantaneously adjust. By contrast, using a need-based noneconomic approach that ignores market mechanisms and assumes that supply is fixed, 565 counties are found to have a nursing shortage. The two methods agree in only 133 cases. Regression estimates indicate that about a third of the counties have a surplus of nurses, suggesting that enough nurses are being trained, but they are not moving from shortage to surplus areas. The average predicted equilibrium nursing wage is $22,084; the average wage from the data is $21,469.